How Self-regulating can it be? Explaining Limitations in Firms’ Compliance with Reflexive Regulation - Bjarke Refslund (International Review of Public Policy)
The article investigates whether reflexive regulation, which emphasizes the regulatee’s ability to self-regulate – and in particular to adapt their organizational structure and behavior to the regulators’ prescriptive goals – leads to companies behaving in the way prescribed by the regulator. Five conditions, which can explain why companies comply or do not comply with reflexive regulation, are specified and then tested empirically. The findings show that almost half of the companies did not comply, or complied only partly, with the reflexive regulation, and that for companies to comply with reflexive regulation certain conditions are salient, including worker involvement, professionalization, and management support. The overall results highlight the limitations of a self-regulatory approach and stress the heterogeneity of companies.